(untitled) (Scientific journal of the Fergana State University, 2023)
The aim of this work is the synthesis of a new organic compound 3,3’-disulfanidylbis(1Н-1,2,4-triazole-5-amine) from 3-amino-5-mercapto-1,2,4-triazole. The article presents the optimal method for the synthesis of 3,3’-disulfanidylbis(1Н-1,2,4-triazole-5-amine) from 3-amino-5-mercapto-1,2,4-triazole and its significance. The results of infrared and Raman spectroscopic analysis of 3-amino-5-mercapto-1,2,4-triazole and 3,3’-disulfanidylbis(1H-1,2,4-triazole-5-amine) are presented.